A new Valorization Route of Petrochemical Wastewater: Recovery of Phenolic Derivatives and their Subsequent Application in a PP Matrix for the Improvement of their Durability in Multiple Applications (2023)
Wastewater from industrial processes contains different compounds that can be of great use to improve its circularity. The potential of wastewater can be exploited by applying extraction techniques to obtain compounds of interest and recircu late them in the process. In this study, the residual water generated during the polypropylene deodorization process was evaluated. The residues of the additives used during the synthesis of the resin are extracted from these waters. With this recovery, contamination of water bodies is avoided and the circularity of the polymer production process is increased.Solid phase extraction and HPLC were used to recover the phenolic compound, obtaining a recovery of more than 95%. FTIR and DSC were applied to evaluate the purity of the extracted compound. Finally, the effectiveness of the phenolic compound was evaluated by applying it to the resin and evaluating its thermal stability by TGA, obtaining as a result, that the recovered additive improves the thermal properties of the material.